1959
DOI: 10.1037/h0043519
|View full text |Cite
|
Sign up to set email alerts
|

Post-hospital adjustment as predicted by psychiatric patients and by their staff.

Abstract: Predischarge ratings were used by a group of psychiatric patients to predict rehospitalization and work, family, and health adjustment for a period of 2 years following hospitalization. Predictions were derived from human interactions and not from psychological tests. Patients could not make predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…The finding that patients as a group were in general more optimistic than staff about their fellow patients' future functioning accords with previous research (Lasky et al 1959), and reflects the tendency for patients to have unrealistically high expectations at discharge (Rychtarik, et al 1992). This may limit the patient's objectivity and isolate them from factual or statistical considerations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding that patients as a group were in general more optimistic than staff about their fellow patients' future functioning accords with previous research (Lasky et al 1959), and reflects the tendency for patients to have unrealistically high expectations at discharge (Rychtarik, et al 1992). This may limit the patient's objectivity and isolate them from factual or statistical considerations.…”
Section: Discussionsupporting
confidence: 81%
“…Within a clinical setting only one study (Lasky, et al 1959) has compared staff with peer outcome ratings. In this study, predicted post psychiatric hospital adjustment was examined in relation to relapse, employment and family adjustment and health.…”
Section: Introductionmentioning
confidence: 98%
“…Thus the individual's past record of maladjustment and hospitalization is a good index of the likelihood of future problems. Recall, in this regard, that the incidence or rehospitalization for psychiatric patients was predicted with a correlation of .61 by the weight of the patient's folder (Lasky, Hover, Smith, Bostian, Duffendack, & Nord, 1959). Such correlations help confirm that all sorts of overall, aggregated indices of the relevant past can predict the future, often usefully, but without necessarily illuminating the nature of the linkage and the structure within the domain.…”
Section: Distinguishing Predictability Stability and The Varieties mentioning
confidence: 87%
“…Their results showed that staff members predicted with 70% accuracy on the average. Similar to certain aspects of Lasky et al (1959), the study presented here is concerned with the ability of health professionals to predict aspects of family and community life alluded to by and . However, the present study appears to be unique in its emphasis on the burden of the released mental patient on the family.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…also found that family relationships and community understanding were important factors in the future outlook of hospitalized psychiatric patients. Lasky, Hover, Smith, Bostian, Duffendack, and Nord (1959) in a rare study of its kind investigated the ability of staff members to predict 2-year posthospital adjustment for psychiatric patients. Their results showed that staff members predicted with 70% accuracy on the average.…”
Section: Review Of the Literaturementioning
confidence: 99%